Indonesia - Giving More Weight to Health : Assessing Fiscal Space for Health in Indonesia - World Bank (World Bank, 2012)
This report analyzes fiscal space issues related to government health spending in Indonesia. Fiscal space refers to the ability of a government to increase expenditures for a desired purpose. In all likelihood, and for a variety of reasons, Indonesia will need to boost health spending in the near future as it expands access to care through the expansion of Jamkesmas, the health insurance scheme for the poor and near poor. In addition, projections based on demographic and epidemiological changes in the country indicate there is likely to be a significant increase in the demand and need for health services and more sophisticated care. Despite a tripling of the public budget for health over the past five years, this increased need, combined with the fact that Indonesia remains a comparatively low spender on health, indicates that there will continue to be upward pressure on resources for the health sector in the near future. A number of different drivers of fiscal space for health in Indonesia are discussed in this paper. These include: (i) conducive macroeconomic conditions; (ii) reprioritization of health within the overall government budget; (iii) increasing health-specific foreign aid and grants; (iv) an increase in other health-specific resources; for example, through earmarked taxation or the introduction of premiums for mandatory health insurance; and (v) an increase in the efficiency of government health outlays. In addition to laying out the possibilities for Indonesia with regard to each of these options, relevant international experiences are also highlighted.